2016
DOI: 10.1093/scan/nsw094
|View full text |Cite
|
Sign up to set email alerts
|

Neural correlates of naturalistic social cognition: brain-behavior relationships in healthy adults

Abstract: Being able to infer the thoughts, feelings and intentions of those around us is indispensable in order to function in a social world. Despite growing interest in social cognition and its neural underpinnings, the factors that contribute to successful mental state attribution remain unclear. Current knowledge is limited because the most widely used tasks suffer from two main constraints: (i) They fail to capture individual variability due to ceiling effects and (ii) they use highly simplistic, often artificial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 89 publications
4
29
0
Order By: Relevance
“…55,56 Further work has revealed that interactions characterized by contingent rather than noncontingent actions elicit stronger pSTS activity 69 and that pSTS responses may be increased in response to negative rather than neutral interactions. 61,65 According to additional data, however, comparing negative and positive encounters does not necessarily result in differential pSTS activity, 59,77 suggesting that the region may respond to valenced actions per se rather than negativity in particular. To better understand the functional significance of the pSTS, however, the type of variations in TPEs that can modulate its activity require further investigation.…”
Section: Tpe Processing In the Person-perception Networkmentioning
confidence: 94%
See 4 more Smart Citations
“…55,56 Further work has revealed that interactions characterized by contingent rather than noncontingent actions elicit stronger pSTS activity 69 and that pSTS responses may be increased in response to negative rather than neutral interactions. 61,65 According to additional data, however, comparing negative and positive encounters does not necessarily result in differential pSTS activity, 59,77 suggesting that the region may respond to valenced actions per se rather than negativity in particular. To better understand the functional significance of the pSTS, however, the type of variations in TPEs that can modulate its activity require further investigation.…”
Section: Tpe Processing In the Person-perception Networkmentioning
confidence: 94%
“…For example, comparing TPEs of positive and negative valence has mainly revealed contradictory results. Even though at least three studies have found enhanced DMPFC activity in response to negative compared with neutral or positive encounters, others have reported null findings or the opposite result. Recent work on the detection of intentional harm in human encounters indicates, however, that simply distinguishing between positive and negative encounters may not suffice to decipher meaningful neural responses.…”
Section: Tpe Processing In the Mentalizing Networkmentioning
confidence: 97%
See 3 more Smart Citations